Pengaruh Pupuk Majemuk NPKS dan NPK terhadap Pertumbuhan dan Hasil Padi Sawah pada Inceptisol - Hartatik, Wiwik; Widowati, Ladiyani Retno (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
Rate of NPK fertilization on rice using NPK compound fertilizer needs to consider soil nutrient status and plant nutrient requirement. The research was aimed to determine the optimum rate of compound fertilizer and the effect of enriched S nutrient of NPKS compound (15-15-15-5S) and NPK compound fertilizer (15-15-15) on the growth and yield of rice. The experiments were conducted at two sites in Galuga, Ciampea Bogor, West Java from April to September 2013, using randomised complete block design with 3 replications. Experiment at site I consisted of 9 treatments: six levels of fertilizers NPKS i.e. 0; 150; 300; 450; 600; and 750 kg/ha, standard fertilizer, NPK compound fertilizer equivalent to standard, and standard fertilizer plus S. Rate of urea, SP-36, and KCl for standard fertilizer treatment was respectively 250, 75, and 50 kg/ha. At site II the treatments consisted of 6 levels of NPK compound fertilizer i.e. 0; 150; 300; 450; 600; and 750 kg/ha and the standard fertilizer with rate of 250 kg/ha of urea, 50 kg/ha SP-36, and 75 kg/ha KCl. Plot size was 4 m x 5 m planted with Ciherang variety. Data collection included chemical properties of soil before and after the experiment, plant height, number of tillers, straw weight, and dry grain weight and the nutrient uptake. The effectiveness of fertilizer was calculated by RAE (Relative Agronomic Effectiveness). Results showed that fertilizer NPKS (15-15-15-5S) at 600 kg/ha effectively increased dry grain weight from 3.63 t/ha to 4.67 t/ha, but was not significantly different from a standard fertilizer treatment. It increased dry grain weight by 29% compared to control. NPK fertilizer (15-15-15) effectively promoted growth and dry grain weight equivalent to standard fertilizer at rate of 300-750 kgha. The optimum rate of NPK compound fertilizer (15-15-15) was 440 kg/ha as was shown with the production performance of 4.12 t/ha with RAE by 58%. NPKS compound fertilizer with rate of 750 kg/ha showed the highest uptake of N, P, and K nutrients and significantly increased the available P in the soil. Whereas NPK compound fertilizer with a rate of 600 kg/ha indicated the highest P nutrient uptake. Fertilizer enrichment with sulfur on NPKS fertilizer (15-15-15-5S) did not significant affect on grain dry weight.